2018
DOI: 10.1371/journal.pone.0207518
|View full text |Cite
|
Sign up to set email alerts
|

A new Seasonal Difference Space-Time Autoregressive Integrated Moving Average (SD-STARIMA) model and spatiotemporal trend prediction analysis for Hemorrhagic Fever with Renal Syndrome (HFRS)

Abstract: Hemorrhagic fever with renal syndrome (HFRS) is a naturally-occurring, fecally transmitted disease caused by a Hantavirus (HV). It is extremely damaging to human health and results in many deaths annually, especially in Hubei Province, China. One of the primary characteristics of HFRS is the spatiotemporal heterogeneity of its occurrence, with notable seasonal differences. In view of this heterogeneity, the present study suggests that there is a need to focus on trend simulation and the spatiotemporal predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
0
17
0
2
Order By: Relevance
“…In these models, the spatial relationships among cities typically have been downplayed. Facing new infectious diseases (e.g., COVID-19) with limited prior knowledge of their features and also limited associated comparability with previous diseases, there has been much uncertainty in setting the theoretical parameters and assumptions of mathematical prediction models 12 15 . Knowledge uncertainty such as this could possibly have led to the highly mixed and uncertain conclusions among the above, existing studies.…”
Section: Introductionmentioning
confidence: 99%
“…In these models, the spatial relationships among cities typically have been downplayed. Facing new infectious diseases (e.g., COVID-19) with limited prior knowledge of their features and also limited associated comparability with previous diseases, there has been much uncertainty in setting the theoretical parameters and assumptions of mathematical prediction models 12 15 . Knowledge uncertainty such as this could possibly have led to the highly mixed and uncertain conclusions among the above, existing studies.…”
Section: Introductionmentioning
confidence: 99%
“…Chang Qi et al [ 35 ] compared the differences in fitting and prediction accuracies of SARFIMA and SARIMA when applied to HFRS disease and found that the SARFIMA model outperforms the SARIMA model in terms of improving the forecast of monthly HFRS cases. Youlin Zhao et al [ 36 ] demonstrated that the SD-STARIMA model offers noticeably better prediction accuracy than the traditional approach, especially for spatiotemporal series data with seasonality characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The disease was thought to be transmitted to humans by inhaling aerosolized excreta of infected animals, or through direct contact with infected rodents and their feces, saliva or blood [ 7 ]. The major clinical manifestations of HFRS include fever, hemorrhage and renal failure [ 8 ]. HFRS is widely distributed in the world with China reporting the highest incidence [ 9 ].…”
Section: Introductionmentioning
confidence: 99%